Songquest The Journals of Great Lakes Folklorist Ivan H. Walton - Walton, Ivan H. (Wayne State University Press, 2018)
Ivan H. Walton was a pioneering folklorist who collected the songs and stories of aging sailors living along the shores of the Great Lakes in the 1930s. His collection is unique in the annals of Great Lakes folklore. It began as a search for songs but broadened into a collection of weather signs, shipboard beliefs, greenhorn tales, and stories of the intense rivalry between sailors and the steamboat men who replaced them. Edited by Joe Grimm, Songquest: The Journals of Great Lakes Folklorist Ivan H. Walton is a selection from the daily journals Walton wrote during his travels as a folklore collector. It is clear that Walton, a professor of English at the University of Michigan, both admired the sailors of the Great Lakes for what they had done during their working years and worried about them as they entered the twilight of their lives. Walton went beyond the songs he set out to find and captured the pitch and roll of the Great Lakes alive with white-winged schooners. His writings provide a clear picture of the colorful individuals he met and interviewed-captains, cabin boys, tugmen, chandlers, boardinghouse owners, dredgers, and light keepers. Walton also documented the methods he used and recorded his personal thoughts about his nomadic life and the events going on around him during the 1930s, including the Great Depression, Franklin D. Roosevelt's election, and the end of Prohibition.